Effective Guest Inclusion by a 6‐O‐Modified β‐Cyclodextrin Dimer in Organic Solvents. Issue 9 (13th September 2018) - Asahara, Chizuru; Iwamoto, Takuya; Akashi, Mitsuru; Shigemitsu, Hajime; Kida, Toshiyuki
Abstract: A 6‐ O ‐ tert ‐butyldimethylsilylated β‐cyclodextrin (TBDMS‐β‐CD) dimer, in which two TBDMS‐β‐CD rings are connected in a head‐to‐head fashion by a m ‐xylylene linker, effectively forms inclusion complexes with pyrene and naphthalene in nonpolar organic solvents such as cyclohexane and benzene. This TBDMS‐β‐CD dimer shows a higher inclusion ability toward these guests than a TBDMS‐β‐CD dimer bearing a p ‐xylylene linker due to the greater cooperation of the two TBDMS‐β‐CD rings for the guest inclusion. Unlike the corresponding monomer, the TBDMS‐β‐CD dimer bearing a m ‐xylylene linker is also a good host even in polar organic solvents such as tetrahydrofuran. High chiral recognition of aromatic amines and alcohol is realized by utilizing inclusion within the cavity of the TBDMS‐β‐CD dimer in cyclohexane. In particular, an extremely high binding selectivity for ( S )‐1‐(1‐naphthyl)ethylamine and ( S )‐1‐(1‐naphthyl)ethanol over the corresponding ( R )‐isomers is achieved. Moreover, by utilizing the high chiral recognition with the TBDMS‐β‐CD dimer in cyclohexane, a non‐enzymatic kinetic resolution of racemic 1‐(1‐naphthyl)ethylamine via enantioselective N ‐benzoylation is attained with an enantiomer excess of up to 87 % and an s ‐factor of 15. Abstract : Be my guest ! A 6‐ O ‐ tert ‐butyldimethylsilylated β‐CD (TBDMS‐β‐CD) dimer forms inclusion complexes with pyrene, naphthalene and chiral naphthalene derivatives in organic solvents such as cyclohexane, benzene and THF. Kinetic resolution of racemic naphthylethylamine through the selective sequestration of the one enantiomer was attained.